Metabolic Checkpoints in Differentiation of Helper T Cells in Tissue Inflammation - Roy, Suyasha; Rizvi, Zaigham Abbas; Awasthi, Amit (Frontiers in Immunology, 2019)
Naïve CD4+ T cell differentiate into effector and regulatory subsets of helper T (Th) cells in various pathophysiological conditions and modulate tissue inflammation in autoimmune diseases. While cytokines play a key role in determining the fate of Th cells differentiation, metabolites, and metabolic pathways profoundly influence Th cells fate and their functions. Emerging literature suggests that interplay between metabolic pathways and cytokines potentiates T cell differentiation and functions in tissue inflammation in autoimmune diseases. Metabolic pathways, which are essential for the differentiation and functions of Th cell subsets, are regulated by cytokines, nutrients, growth factors, local oxygen levels, co-activation receptors, and metabolites. Dysregulation of metabolic pathways not only alters metabolic regulators in Th cells but also affect the outcome of tissue inflammation in autoimmune and allergic diseases. Understanding the modulation of metabolic pathways during T cells differentiation may potentially lead to a therapeutic strategy for immune-modulation of autoimmune and allergic diseases. In this review, we summarize the role of metabolic checkpoints and their crosstalk with different master transcription factors and signaling molecules in differentiation and function of Th subsets, which may potentially unravel novel therapeutic interventions for tissue inflammation and autoimmune disorders.